Reflections on genealogies, memory and writing of women: experiences and words exposed (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2019)
The genealogies of women help to rescue the biographical profiles and inheritances received from our ancestors in different times, cultures and societies. They constitute a research method to reestablish the threads of memory, revise historical narratives from feminist approaches and highlight diversities, singularities and fissures in the face of globalizing theories and the hegemonic manifestations of power. The article, presented in line with the latest debates on Biography and Autobiography as a historical-literary genre, shows women’s capacity to act as agents of change, resistance and opposition, contributes to establish the processes of construction / deconstruction of identities and emphasizes the female protagonism in the production of historical sources.
Keywords: genealogies; feminisms; memory; biographies; autobiographies